2013
DOI: 10.1007/s12013-013-9695-4
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Endophytic Fungus, Chaetomium globosum JN711454, as Potential Candidate for Improving Drug Discovery

Abstract: The main objective of this research work focused on investigating the biological and chemical aspects of endophytic fungus Chaetomium globosum, for pharmaceutical purposes to improve the drug discovery process. The endophytic C. globosum was isolated from healthy leaves of Egyptian medicinal plant Adiantum capillus-veneris collected from Saint Katherine Protectorate, Sinai, Egypt. The identification of C. globosum was on the basis of classical and molecular taxonomy. Gene encoding for 18S rRNA was partially se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Accordingly, we concluded that the host-microbe interaction is one of the driving forces for endophytic secondary metabolites production [3][4][5]8]. The previous results confirmed that C. globosum was considered as a promising source of bioactive metabolites which could be used in drug industry [10].…”
Section: Antioxidant and Antiviral Activitiesmentioning
confidence: 56%
See 4 more Smart Citations
“…Accordingly, we concluded that the host-microbe interaction is one of the driving forces for endophytic secondary metabolites production [3][4][5]8]. The previous results confirmed that C. globosum was considered as a promising source of bioactive metabolites which could be used in drug industry [10].…”
Section: Antioxidant and Antiviral Activitiesmentioning
confidence: 56%
“…Of all the 99 crude extracts, only Chaetomium globosum isolated from the internal tissues of Adiantum capillus-veneris revealed a promising antioxidant activity (99%) DPPH scavenging activity at the level 100 µg/mL of total extract (Table 2). Genetic identification (18S rDNA) of the active antioxidant isolate was achieved in our previous report [10]. It showed a high similarity to Chaetomium globosum.…”
Section: Antioxidant and Antiviral Activitiesmentioning
confidence: 91%
See 3 more Smart Citations